Offshore Technology Conference 2006
DOI: 10.4043/17872-ms
|View full text |Cite
|
Sign up to set email alerts
|

Tension/Torsion Behavior of Deepwater Synthetic Mooring Lines

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractSynthetic fiber ropes are now being used in mooring systems off Brazil and in the Gulf of Mexico, and are being considered for deepwater handling applications. Their behavior under tension loads is well understood but induced torsion effects have received less attention. This paper presents tests to measure induced torque in full size steel, aramid and polyester wire ropes. Results are compared with model predictions and good correlation is obtained. A specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…The same relative classification of the post bedding-in strain for each BI was expected. It has been observed previously (Davies et al, 2006;Humeau, 2017;Liu et al, 2014) that the rope's construction influences the bedding-in behavior. The fact that filament post bedding-in strain is not zero shows that the material (fiber) history also influences the global behavior.…”
Section: Comparisonmentioning
confidence: 86%
See 1 more Smart Citation
“…The same relative classification of the post bedding-in strain for each BI was expected. It has been observed previously (Davies et al, 2006;Humeau, 2017;Liu et al, 2014) that the rope's construction influences the bedding-in behavior. The fact that filament post bedding-in strain is not zero shows that the material (fiber) history also influences the global behavior.…”
Section: Comparisonmentioning
confidence: 86%
“…These models are based on the geometries and the properties of each scale, and friction is also considered in some of them. (Davies et al 2006) applied Leech's model and found a good correlation of tension/torsion properties for results on full size long rope samples. Braided ropes have received less attention than stranded ropes, but some researchers have investigated behavior models, in particular (Rawal et al, 2015;Vu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Failure of one or several elements may cause the adjacent elements to fail immediately, resulting in either complete failure or strength loss. Further details can be found in [22][23][24][25].…”
Section: Rope Modellingmentioning
confidence: 99%
“…Leech has developed a modeling framework, which takes into account both the helical geometry and the nonlinear force-strain response of the yarns in a hierarchical modeling approach (Leech, 2002). This is available in a commercial package known as Fiber Rope Modeller, which has proved effective in modeling the tensile response of large rope structures (Leech et al, 1993(Leech et al, , 2003Davies et al, 2006).…”
Section: Aging Of Ropes In Servicementioning
confidence: 99%